Solid electrolyte, all-solid battery, and method for producing the same

By forming thin film-like dense mass on the surface of porous mass, the problem of insufficient strength of thin dense mass is solved, and efficient manufacturing of solid electrolytes and all-solid batteries is achieved, thereby improving the stability and performance of the battery.

CN111684641BActive Publication Date: 2025-01-07JAPAN FINE CERAMICS
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN201980011878.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-08
Filing Date
2019-02-07
Publication Date
2025-01-07
Estimated Expiration
2039-02-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively produce a thin dense solid electrolyte with a thickness of less than 100 μm. Because its thinness leads to insufficient strength, it is difficult to avoid crack defects, which will affect the manufacturing of all-solid batteries.

Method used

By producing a porous body composed of the first ceramic, and forming a film-like dense body composed of the second ceramic on its surface, the integration of the two is achieved through the firing technology, and the strength of the film-like dense body is improved.

Benefits of technology

It realizes easy production of thin dense mass bodies, and improves the manufacturing efficiency of solid electrolytes and all-solid batteries, ensuring the stability and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111684641B_ABST
    Figure CN111684641B_ABST
Patent Text Reader

Abstract

The present invention provides a solid electrolyte body, a fully solid battery, and a method for manufacturing the same. The solid electrolyte body and the like can be used to easily manufacture a thin film solid electrolyte body and the like. A porous body (110) is manufactured by manufacturing a molded body (11) of a first ceramic and firing the molded body (11) at a first temperature. A thin film molded body (12) composed of a second ceramic containing a solid electrolyte is manufactured on at least a portion of the surface of the porous body (110). A dense body (120) is manufactured by firing the thin film molded body (12). As a result, a solid electrolyte body (1) having a porous body (110) as a support body and a dense body (120) of a thin film electrolyte can be manufactured, wherein the dense body (120) is integrally formed on at least a portion of the surface of the porous body (110).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for producing a solid electrolyte body and a method for producing an all-solid-state battery using the solid electrolyte body. Background Art

[0002] A method for manufacturing a solid electrolyte for an all-solid-state battery is proposed (see Patent Document 1). Specifically, a first ceramic material containing a solid electrolyte (e.g., Li3PO4, LiPON, Li2S-SiS2, Li2S-P2S5, Li2S-B2S3, etc.) is formed into a plate to obtain a first molded body, and a dense body is formed by firing the first molded body. A second molded body is obtained by applying a second ceramic material containing a solid electrolyte that is the same as or different from the solid electrolyte constituting the dense body to one surface of the dense body, and the second molded body is additionally fired together with the dense body at a temperature lower than the firing temperature of the first molded body, thereby forming a fired integrated porous layer on at least one surface of the dense body.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent No. 5281896 Summary of the invention

[0006] Problems to be solved by the invention

[0007] According to the above-mentioned prior art, the first molded body is obtained by a pressing method, a doctor blade method, a reverse roll coating method, etc., thereby obtaining a solid electrolyte having a dense body with a thickness of 5 μm to 100 μm. However, in fact, although it is not impossible to produce a thin dense body solid electrolyte with a thickness of less than 100 μm, it is difficult to produce it because the insufficient strength caused by its own thinness will cause cracks and defects.

[0008] Therefore, an object of the present invention is to provide a method for manufacturing a solid electrolyte body and a method for manufacturing an all-solid-state battery, etc., which can facilitate the production of a thin, dense solid electrolyte.

[0009] Means for solving problems

[0010] The present invention relates to a method for manufacturing a solid electrolyte body, which comprises: a porous body composed of a first ceramic; and a thin film-shaped dense body composed of a second ceramic containing a solid electrolyte, wherein the dense body is formed integrally with at least a portion of the surface of the porous body and contains a solid electrolyte.

[0011] The method for manufacturing a solid electrolyte body of the present invention is characterized in that it includes: a process of preparing a first molded body and preparing the porous body by sintering the first molded body; and a process of preparing a thin film-like second molded body of the ceramic on at least a portion of the surface of the porous body, and preparing a dense body containing the solid electrolyte by sintering the second molded body.

[0012] The manufacturing method of the all-solid-state battery of the present invention is characterized in that it includes: a process of manufacturing the solid electrolyte body using the manufacturing method of the solid electrolyte body of the present invention; and a process of filling the open pores of the porous body constituting the solid electrolyte body with an active material serving as an electrode.

[0013] Effects of the Invention

[0014] According to the method for manufacturing a solid electrolyte body and a method for manufacturing an all-solid battery of the present invention, a second molded body in the form of a thin film is formed on at least a portion of the surface of a previously manufactured porous body, and a dense body containing a thin film solid electrolyte is manufactured by firing the second molded body. Therefore, it is possible to manufacture a solid electrolyte body and an all-solid battery while facilitating the manufacture of a thin dense body.

[0015] Brief description of the attached figure

[0016] Figure 1A It is an explanatory diagram regarding the production process of the first molded body.

[0017] Figure 1B This is a diagram for explaining the steps of producing a porous body.

[0018] Figure 1C It is an explanatory diagram regarding the production process of the second molded body.

[0019] Figure 1D This is a diagram for explaining the production process of a dense mass.

[0020] Figure 2A It is an explanatory diagram regarding the production process of the first electrode.

[0021] Figure 2B It is an explanatory diagram regarding the production process of the second electrode.

[0022] Figure 2C This is a diagram for explaining the process of joining electrodes and current collectors.

[0023] Figure 3A It is an explanatory diagram regarding the structure of a solid electrolyte body according to another embodiment.

[0024] Figure 3B It is an explanatory diagram regarding the structure of an all-solid-state battery according to another embodiment. DETAILED DESCRIPTION

[0025] (Solid Electrolyte Structure)

[0026] like Figure 1D As shown, a solid electrolyte body 1 manufactured by a method as one embodiment of the present invention includes a flat porous body 110 and a dense body 120 containing a thin film solid electrolyte in close contact with one main surface of the porous body 110 .

[0027] The porous body 110 is composed of a first ceramic that is not a lithium ion electrolyte, and has a plurality of open pores 112, and the open pores 112 constitute a passage connecting from one main surface to another main surface. The thickness of the porous body 110 is, for example, in the range of 100 μm to 1 mm or in the range of 100 μm to 500 μm. The porosity of the porous body 110 is, for example, in the range of 10 to 70 vol.% or in the range of 20 to 50 vol.%. The porosity is measured by mercury penetration.

[0028] For example, partially stabilized zirconia may be used as the first ceramic of the non-lithium ion electrolyte.

[0029] It should be noted that the first ceramic may also contain a lithium ion solid electrolyte. The solid electrolyte may be, for example, a lithium ion conductive glassy solid electrolyte represented by Li3PO4, LiPON mixed with nitrogen in Li3PO4, Li2S-SiS2, Li2S-P2S5, Li2S-B2S3, or a lithium ion conductive solid electrolyte doped with lithium halides such as LiI or lithium chlorates such as Li3PO4 in these glasses, or a solid electrolyte containing lithium as an active ion. For example, Li x La y TiO3 (0<x<1, 0<y<1 (e.g. x=0.35 / y=0.55)), phosphate compounds, Li 1+x Al x Ti 2-x Titanium oxide-type solid electrolytes containing lithium, titanium and oxygen, such as (PO4)3, show stable performance even when fired in an oxygen atmosphere.

[0030] The dense body 120 is composed of the second ceramic containing the above-mentioned solid electrolyte. The thickness of the dense body 120 is not limited, and is, for example, within the range of 0.5 μm to 100 μm. The solid electrolyte contained in the first ceramic and the solid electrolyte contained in the second ceramic may be the same or different.

[0031] (Method for producing solid electrolyte body)

[0032] A method for producing a solid electrolyte body as one embodiment of the present invention includes (S1) a step of producing a first molded body, (S2) a step of producing a porous body, (S3) a step of producing a second molded body, and (S4) a step of producing a dense body.

[0033] In step (S1), a first molded body 11 (see Figure 1A As a method for producing the first molded body 11, for example, a sheet forming method or a roll pressing method is used. For example, a binder such as butyral resin is mixed and prepared into a paste, and the first molded body 11 is produced by the above method.

[0034] In order to adjust the porosity and pore diameter of the porous body 110, a pore former such as starch or carbon may be added to the first ceramic, and when the first molded body 11 is fired, the pore former disappears to form open pores 112. The thickness of the porous body 110 obtained by firing is, for example, within the range of 100 μm to 1 mm or within the range of 100 μm to 500 μm.

[0035] In step (S2), the first molded body 11 is fired in the first temperature range to produce a porous body 110 (see Figure 1B ). Many open pores 112 are formed by the decomposition and shedding of the binder and pore-forming agent contained in the raw material, which are three-dimensionally connected from one main surface of the porous body 110 to the other main surface. The first temperature range is set according to the types of the first ceramic, the binder and the pore-forming agent, for example, in the range of 800 to 1500°C, or in the range of 1000 to 1300°C. As described later, in step (S4), the porous body 110 is exposed to a temperature environment included in the second temperature range. Therefore, in order to avoid excessive reduction in porosity due to over-firing of the porous body 110, the sintering time is preferably controlled in the range of, for example, 1 to 5 hr (hours), for example, 2 to 3 hr (hours).

[0036] In step (S3), a second molded body 12 (see FIG. 1 ) in a thin film shape made of a material containing a second ceramic is formed on one main surface of the porous body 110. Figure 1C ). As a method for producing the second molded body 12, a coating method such as a paste printing method, a CVD method, a sputtering method, an aerosol deposition method, etc. is used. The thickness of the second molded body 12 is not limited, and is, for example, within the range of 0.5 μm to 100 μm, or 5 μm to 30 μm.

[0037] In step (S4), the second molded body 12 is fired in the second temperature range to form a dense body 120 (see Figure 1D). The second temperature range is, for example, in the range of 900 to 1500° C. or in the range of 1000 to 1300° C. In the case where the first ceramic and the second ceramic are the same, a necking phenomenon of the first ceramic and the second ceramic is easily formed at the connection interface between the porous body 110 and the dense body 120, thereby achieving an improvement in the bonding strength between the porous body 110 and the dense body 120. In order to avoid an excessive reduction in porosity due to over-firing of the porous body 110, the sintering time is preferably controlled in the range of 1 to 5 hours, for example, in the range of 2 to 3 hours.

[0038] After the above steps (S1) to (S4), Figure 1D As shown, a solid electrolyte body 1 including a porous body 110 and a dense body 120 is produced, wherein the dense body 120 is formed integrally with the porous body 110 on one main surface of the porous body 110 .

[0039] (Composition of all-solid-state batteries)

[0040] As an embodiment of the present invention, Figure 2C As shown, the all-solid-state battery 2 manufactured by this method has Figure 1D The solid electrolyte body 1 shown, the first electrode 21 , the second electrode 22 , the first electrode collector 41 electrically connected to the first electrode 21 , and the second electrode collector 42 electrically connected to the second electrode 22 .

[0041] The first electrode 21 is formed by an active material filled in the open pores 112 of the porous body 110 constituting the solid electrolyte body 1. When the first electrode 21 is a positive electrode, the following materials can be used as the active material (positive electrode active material): manganese dioxide (MnO2), iron oxide, copper oxide, nickel oxide, lithium manganese composite oxide (for example, Li x Mn2O4 or Li x MnO2) (e.g., 1<x<5 (the same below)), lithium nickel composite oxide (e.g., Li x NiO2), lithium cobalt composite oxides (such as Li x CoO2), lithium nickel cobalt composite oxides (e.g., LiNi 1-y Co y O2) (e.g., 0<y<1 (the same below)), lithium manganese cobalt composite oxide (e.g., LiMn y Co 1-y O2), spinel lithium manganese nickel composite oxide (e.g., Li x Mn 2-y Ni y O4), lithium phosphate compounds with olivine structure (such as Li x FePO4, Li x Fe1-y Mn y PO4、Li x CoPO4), lithium phosphate compounds with NASICON structure (e.g., Li x V2(PO4)3), iron sulfate (Fe2(SO4)3), vanadium oxide (for example, V2O5), etc. Electronic conductivity aids such as acetylene black, carbon black, graphite, various carbon fibers, carbon nanotubes, etc. may also be added to the positive electrode active material.

[0042] When the first electrode 21 is a negative electrode, the active material (negative electrode active material) may include: carbon, metallic lithium (Li), metal compounds, metal oxides, Li metal compounds, Li metal oxides (including lithium-transition metal composite oxides), boron-added carbon, graphite, compounds having a NASICON structure, etc.

[0043] As carbon, for example, conventionally known carbon materials such as graphite carbon, hard carbon, and soft carbon can be used. As metal compounds, LiAl, LiZn, Li3Bi, Li3Cd, Li3Sd, Li4Si, Li 4.4 Pb、Li 4.4 Sn、Li 0.17 C (LiC6), etc. Examples of metal oxides include SnO, SnO2, GeO, GeO2, In2O3, In2O3, PbO, PbO2, Pb2O3, Pb3O4, Ag2O, AgO, Ag2O3, Sb2O3, Sb2O4, Sb2O5, SiO, ZnO, CoO, NiO, TiO2, FeO, etc. Examples of Li metal compounds include Li3FeN2, Li 2.6 Co 0.4 N.Li 2.6 Cu 0.4 N, etc. As Li metal oxides (lithium-transition metal composite oxides), Li4Ti5O 12 The boron-added carbon includes boron-added carbon, boron-added graphite, etc. In the negative electrode active material, the conductive auxiliary agent as described above may be added to the positive electrode active material.

[0044] The second electrode 22 is formed by molding an electrode material containing an active material into a film or sheet having a predetermined thickness.

[0045] The materials used to form the first electrode collector 41 and the second electrode collector 42 include, for example, general electronically conductive metal materials such as platinum (Pt), platinum (Pt) / palladium (Pd), gold (Au), silver (Ag), aluminum (Al), copper (Cu), ITO (indium-tin oxide film), and SUS plates.

[0046] (Method for manufacturing all-solid-state battery)

[0047] The method for manufacturing a fully solid-state battery as one embodiment of the present invention includes the following steps in addition to the steps (S1) to (S4) of the method for manufacturing a solid electrolyte body as one embodiment of the present invention: (S5) a step of filling the open pores 112 of the porous body 110 with an active material; (S6) a step of sintering the active material to form the first electrode 21; (S7) a step of forming the second electrode 22; (S8) a step of connecting the first electrode collector 41 to the first electrode 21; and (S9) a step of connecting the second electrode collector 42 to the second electrode 22. Here, the description of the steps (S1) to (S4) is omitted.

[0048] In step (S5), the open pores 112 of the porous body 110 constituting the solid electrolyte body 1 are filled with an active material. The active material may be, for example: an active material such as a positive electrode active material or a negative electrode active material that is micronized and dispersed in an organic solvent, an aqueous solvent, pure water, or the like to form a colloidal active material; a solution in which the active material is sol-formed, etc. For example, the open pores 112 of the porous body 110 are filled with the active material by dripping or immersing the sol-form active material on the surface of the porous body 110 in the air, in an Ar atmosphere, or in a vacuum. In the case where the open pores 112 of the porous body 110 are not sufficiently filled with the active material, the filling operation may be repeated multiple times.

[0049] In step (S6), the active material is fired as needed to form the first electrode 21 (see Figure 2A The firing temperature when firing the active material is controlled within a range of 700 to 1100° C., for example. However, when an electron conductivity aid such as carbon is added, firing is not preferred, and thus this step ( S6 ) is omitted.

[0050] In step (S7), after forming the second electrode 22 by a coating method such as a paste printing method or a roll coating method, the second electrode 22 is fired as needed in the same manner as described above. The second electrode 22 may also be formed by a method such as a sputtering method, a resistance heating evaporation method, an ion beam evaporation method, or an electron beam evaporation method.

[0051] In step (S8), the first electrode current collector 41 is formed in a state where the first electrode 21 is connected to the first electrode 21 by a method such as sputtering, ion beam deposition, or electron beam deposition (see Figure 2CIn step (S9), the second electrode current collector 42 is formed in a state where the second electrode current collector 42 is connected to the second electrode 22 by a method such as sputtering, ion beam evaporation, or electron beam evaporation (see Figure 2C ). It should be noted that step (S8) and step (S9) may be omitted.

[0052] After the steps (S1) to (S9) or the steps (S1) to (S5) and (S7) to (S9), Figure 2C As shown, an all-solid-state battery 2 is manufactured, which comprises: a porous body 110; a dense body 120 formed integrally with the porous body 110 on one main surface of the porous body 110; a first electrode 21 at least part of which is composed of an active material filled in open pores 112 of the porous body 110; a second electrode formed on the other main surface of the dense body 120; a first electrode collector 41 electrically connected to the first electrode 21; and a second electrode collector 42 electrically connected to the second electrode 22.

[0053] (Effect)

[0054] According to the method of the present invention, a thin film-like second molded body 12 is formed on at least a portion of the surface of a previously manufactured porous body 110, and the second molded body 12 is fired to manufacture a thin film-like dense body 120 (see Figure 1C and Figure 1D ). Therefore, the solid electrolyte body 1 and the all-solid battery 2 can be manufactured while facilitating the production of the thin dense body 120.

[0055] (Other embodiments of the present invention)

[0056] like Figure 3A As shown in FIG. 1 , a solid electrolyte body 1 having a pair of porous bodies 110 and a dense body 120 sandwiched between the pair of porous bodies 110 may be formed. For example, after forming a pair of porous bodies 110, a second molded body 12 is formed on one main surface of one of the porous bodies 110 (see FIG. 1 ). Figure 1C On this basis, one main surface of another porous body 110 is brought into contact with the second molded body 12, and the second molded body 12 sandwiched by a pair of porous bodies 110 is manufactured, and then fired to obtain Figure 3A The solid electrolyte shown.

[0057] You can also use Figure 3A The solid electrolyte body 1 shown in the figure is produced through steps (S5), (S6), (S8) and (S9), or through steps (S5), (S8) and (S9) Figure 3BThe all-solid-state battery 2 shown. In this case, steps (S8) and (S9) may be omitted.

[0058] Explanation of symbols

[0059] 1…solid electrolyte body, 2…all-solid-state battery, 11…first molded body, 12…second molded body, 21…first electrode, 22…second electrode, 41…first electrode current collector, 42…second electrode current collector, 110…porous body, 112…open pores, 120…dense body.

Claims

1. A method for producing a solid electrolyte body, the solid electrolyte body comprising: a porous body composed of a first ceramic containing a non-lithium ion electrolyte; and a thin film-shaped dense body composed of a second ceramic containing a lithium ion solid electrolyte, wherein: The dense body is formed integrally with at least a portion of the surface of the porous body. The method for producing the solid electrolyte body is characterized by comprising the following steps: Step 1: preparing a first molded body, and preparing the porous body by sintering the first molded body; and Step 2: A second ceramic film-shaped molded body is formed on at least a portion of the surface of the porous body, and the dense body is formed by firing the second molded body.

2. A method for manufacturing an all-solid-state battery, characterized in that: It has the following processes: Step 1: manufacturing the solid electrolyte body by using the method for manufacturing a solid electrolyte body according to claim 1; and Step 2: Filling active material into the pores of the porous body constituting the solid electrolyte body.

3. A solid electrolyte for a lithium battery solid battery, characterized in that: A solid electrolyte body for a lithium battery solid state battery obtained by the method for producing a solid electrolyte body according to claim 1, comprising: A porous body composed of a first ceramic containing a non-lithium ion electrolyte; and a thin film-shaped dense body composed of a second ceramic containing a lithium ion solid electrolyte, The dense body is formed integrally with at least a portion of the surface of the porous body.

4. An all-solid-state battery, characterized in that: The all-solid-state battery obtained by the method for manufacturing an all-solid-state battery according to claim 2 comprises: a first electrode composed of a porous body and an active material, wherein the porous body is composed of a first ceramic of a non-lithium ion electrolyte, and the active material is filled in the pores of the porous body; an electrolyte membrane composed of a thin film-like dense body composed of a second ceramic containing a solid electrolyte and formed integrally with at least a portion of the surface of the porous body; and The second electrode includes an active material and is provided on a surface opposite to the first electrode via the electrolyte membrane.

5. The all-solid-state battery according to claim 4, characterized in that: The second electrode is composed of a porous body and an active material, wherein the porous body is composed of the first ceramic, and the active material is filled in pores of the porous body.

Citation Information

Patent Citations

  • Manual driving device for ship

    JP1977081896A

  • Solid oxide fuel cell, and method of manufacturing same

    JP2006339034A

  • Solid oxide fuel cell

    JP2009259746A

  • Symmetrical, bi-electrode supported solid oxide fuel cell

    US20070065701A1

  • Solid electrolyte structure for all-solid-state battery, all-solid-state battery, and their production methods

    US20090226816A1